2019
DOI: 10.2478/ats-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour, physiology and body mass of Nigerian indigenous hens during brooding

Abstract: This study was conducted to investigate the behaviour, selected physiological indicators and body mass changes in Nigerian indigenous broody hens. The times spent by the hens sitting on eggs and on ingestive behaviours (feeding and drinking) were monitored between 14:00 and 18:00 h twice per week for three weeks. The growth and physiological indicators monitored were body mass, rectal temperature, breast temperature and blood glucose concentration. Data collected were analysed using repeated measures ANOVA of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This implies that once BRD commenced, the hens' behaviors remained consistent irrespective of the stage of development of the embryo, until the chicks hatch. Iyasere et al ( 17 ) also observed consistent sitting on eggs and ingestive behavior in the YRE ecotype over the three weeks of BRD. Broodiness is controlled by the prolactin hormone ( 31 ).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…This implies that once BRD commenced, the hens' behaviors remained consistent irrespective of the stage of development of the embryo, until the chicks hatch. Iyasere et al ( 17 ) also observed consistent sitting on eggs and ingestive behavior in the YRE ecotype over the three weeks of BRD. Broodiness is controlled by the prolactin hormone ( 31 ).…”
Section: Discussionmentioning
confidence: 76%
“…It was our intention to have a minimum of 15 broody hens per ecotype, but within the 7-month experimental period (July 2021 and January 2022), only 10 out of 30 (33.3%) YRE and 5 out of 30 (16.7%) FLE hens became broody. A previous study by Iyasere et al ( 17 ) on BRD behavior, reported a 30% success of the YRE becoming broody in a similar intensive rearing system. The breakdown of when the hens became broody in the current study is as follows; July (three YRE and one FLE), September (three YRE), October (two YRE and one FLE), November (two YRE), and December (three FLE).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The Nigeria native chickens are preferred by the population for their good source of protein, the flavour of their meat and eggs compared to exotic chickens. They are also characterised by their capacities to hatch their eggs, hardy and resistant to diseases (Iyasere et al 2019;Abou Zeid et al 2020). However, the productivity rate of these local chickens remains very low due to inadequate nutrition, poor disease management and unimproved genetic potential in terms of their body weight (Munisi et al 2015).…”
Section: Introductionmentioning
confidence: 99%